Multidimensional detection and dynamic defense method for link flooding attack - Yang WANG; Guangming TANG; Cheng LEI; Dong HAN (网络与信息安全学报, 2019)
Aiming at the shortcomings of the existing link flooding attack defense methods,a multi-dimensional index detection algorithm is proposed,which performs multi-dimensional detection on the abnormal forwarding links through the five-dimensional elements of connection length,low-speed ratio of data packets,uniformity of data packet distance,average low-speed ratio of data packets,and change rate of low-speed ratio of data packets,thus effectively solving the problem of high false alarm rate of the existing detection methods.Furthermore,a controller switch dynamic deployment method based on coloring theory is proposed,which solves the problem of difficult to be actually deployed in the actual environment with limited switch variant types existing in the existing defense mitigation mechanisms.Experimental analysis show the feasibility of the proposed method.